Analysis Of The Impact Of Training, Motivation, And Performance On Employee Productivity Of Pt Food Beverage Indonesia (Chatime Bandung) - Priscilla Simone, Rachel; Teja, Andri Hertanto; Dayona Ismail, Gurawan; Ayu Sofianti , Nunung; Hamdani, Deni (Riviera Publishing, 2026)
Employee productivity is the ability and structured process to produce optimal output through efficient, timely, and quality utilization of resources. Thiis study aiims to empirically test and anallyze the effeect of training, motiivation, and performance on emplloyee productivity, both partially and simultaneously. The metthod usedwin thiis sttudy is a quantitatiive researrch method wiith a descriptiive and veriification approach. Thewdata sourrces usedware priimary datawsourrces and secondarry datawsourrces. Data colllection techniiques in thiis study are interviiews, questionnaires, observations, library research both online and offline. The popullation in thiis study is alll 98 employees, so the samplling techniique used in thiis study is a census samplle or census sampling. The analytical tool in this study is SPSS 25. The data validity technique uses vallidity tests and relliability tests with cllassical assumptiion tests, and data anallysis techniiques use mulltiple regressiion anallysis, correllation anallysis, and determiination anallysis. Hypothesiis testiing uses theututest (partial) andutheuFutest (simultaneous). The resullts of this sttudy are, 1) training has a positiive and signifiicant effeect on employee productivity partially. 2) motivation has a posiitive and signifiicant effeect on employee productivity partially. 3) Performance has a posiitive and significant efffect on employee productivity partially. 4) Trainiing and motivation have a posiitive and signifiicant efffect on employee productivity simultaneously. 5) Training and performance have a positiive and signifiicant efffect on employee productiviity simultaneously. 6) Motiivation anduperformance haveua posiitive and siignificant efffect ongemployee productiivity simultaneously. 7) Trainiing, motivation, and performance have a posiitive and signifiicant efffect on employee productiivity simultaneously, with an effect of 89.3%, with the remaining 10.7% being inflluenced by other variiables not examiined in thiis study.